Examining the impacts of travellers' intrinsic motivation in social media travel sharing behaviour in Indonesia / Elisabet Dita Septiari and Azizah Omar - Septiari, Elisabet Dita; Omar, Azizah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
This study examines the intrinsic motivation factors on social media travel sharing behaviour. The selfdetermination theory has been applied as an underlying research framework of the study. An online survey was sent to 409 millennial Indonesian domestic travellers. Partial least squares (PLS) were conducted to test the research framework model. The findings revealed that intrinsic motivation factors to know, accomplish, and experience stimulation positively impacted social media travel sharing behaviour. The study findings also indicated that experience stimulation had the most significant impact. The results suggested that various types of intrinsic motivation had different effects on different contexts. Hence, the result explained the importance of travel sharing through social media to promote the tourism industry. Tourism companies can enhance their services to facilitate travellers build their cognitive skills and stimulate their emotions, so they voluntarily share their social media experiences. The topic of this study is a combination of research on motivation research and tourist behaviour in the context of social media. It identified how three types of intrinsic motivation affected travel sharing on social media. The result suggested that intrinsic motivation should not be treated as a unitary construct.